The problem of harm in world politics : theoretical investigations - Linklater, Andrew (Cambridge University Press)
"The need to control violent and non-violent harm has been central to human existence since societies first emerged. This book analyses the problem of harm in world politics which stems from the fact that societies require the power to harm in order to de